The Personal growth on adolescent sexual abuse offender who have passed the detention period: Gambaran personal growth pada remaja pelaku kekerasan seksual - Nila Anggreiny; Septi Mayang Sarry; Ira Wahyuni (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Adolescents who believe that they can change are more open to learning, willing to confront challenges, and able to rise from failing, which means personal growth. This research aims to know the process of personal growth in adolescent sexual abuse offenders. The method that was used is qualitative with a phenomenology approach and using the interview as a data collection method. The result of this research describes the personal growth of adolescent sexual abuse offenders marked with three themes of personal growth starting the change, feeling the dissonance, and reorganizing the experience. The personal growth that surfaced is influenced by family, experience, and spiritual factors.